2009
DOI: 10.1002/nau.20780
|View full text |Cite
|
Sign up to set email alerts
|

Open retropubic colposuspension for urinary incontinence in women: A short version cochrane review

Abstract: The evidence available indicates that open retropubic colposuspension is an effective treatment modality for stress urinary incontinence especially in the long term. Within the first year of treatment, the overall continence rate is approximately 85-90%. After 5 years, approximately 70% of patients can expect to be dry. Newer minimal access procedures such as tension free vaginal tape look promising in comparison with open colposuspension but their long-term performance is not known and closer monitoring of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
1
14
1
4
Order By: Relevance
“…Many studies have confirmed its cure rate at 69–88% [3–5]. However, over the past decade this procedure has been largely replaced by the application of various types of TVTs (tension-free vaginal tapes) [611].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have confirmed its cure rate at 69–88% [3–5]. However, over the past decade this procedure has been largely replaced by the application of various types of TVTs (tension-free vaginal tapes) [611].…”
Section: Introductionmentioning
confidence: 99%
“…Many different surgical procedures (colposuspension, traditional slings, and injectables) are commonly used, but these procedures are associated with significant morbidity and resource use or low success rates (2, 3). Tension‐free vaginal tape (TVT) is a standard minimally invasive procedure used to treat urinary stress incontinence since 1995 when it was first described by Ulmsten (4).…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the surgery of choice for treatment of stress UI was open retropubic colposuspension (Burch operation) with a cure rate of 85%-90% after 1 year and 70% after 5 years [16]; for many gynecologists, Burch colposuspension remains the surgery of choice. However, many believe that tension-free vaginal tape (TVT) is a gold standard for the surgical treatment of stress UI because it is minimally invasive, has a short hospital stay or can be conducted as an officebased procedure, has few complications, and a favorable long-term outcome (a 90% cure rate after 11.5 years) [17,18].…”
Section: O M / L O C a T E / I J G Omentioning
confidence: 99%